Diversity and Heterogeneity of Population - Ostasiewicz, Walenty (Dywersyfikacja i zróżnicowanie populacji, 2009)
The paper addresses some problems concerning the diversification of populations. The problem of economic diversification, particularly with respect to income inequality, is reviewed very briefly. The main purpose, however, is to present the recently developed theory of heterogeneity of population with respect to the mortality. The core of this theory has been initiated in 1979, the exposition of it is illustrated by a series of simple examples.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 66, s. 33-41